A Case Study of Inflammatory Arthritis with Progressive Joint Destruction - Evija S; Helena M; Janis A; Dace V (Medical Science: Recent Advances and Applications Vol. 3, 2025)
Rheumatoid arthritis is a systemic inflammatory disease with autoimmune features, with a predominant expression in peripheral synovial joints. A clinical evaluation remains the cornerstone for evaluating early arthritis; determining whether arthritis is present or not, differentiating between the inflammatory or non-inflammatory disease, and deciding on the aetiology of the arthropathy. Rheumatoid factor (RF) and antibodies to citrullinated peptide (ACPA) have been detected in patients with RA years before the onset of symptoms- evidence that the disease process begins in the preclinical phase, before the onset of symptoms. This study presents a case of aggressive rheumatoid arthritis of wrist joints misdiagnosed as infectious arthritis, which has led to the total joint destruction within a period of 3 years. The patient, a 57-year-old female, presented with complaints of severe pain, swelling and functional disorders of the left wrist joint at the beginning of 2013. She started complaining in December 2010 during the flu infection, accompanied by conjunctivitis. The flu lasted for a month and resulted in severe complications. Rheumatoid factor (RF) and antibodies to citrullinated peptide (ACPA) have been detected in patients with RA years before the onset of symptoms- evidence that the disease process begins in the preclinical phase, before the onset of symptoms. In this case, it was noticed in the lab tests that the ACPA antibodies were serologically positive for RF. According to the ACR 2010 criteria, the consultant in rheumatology affirmed the preliminary diagnosis of rheumatoid arthritis. Unfortunately, the delay in confirming the diagnosis and the destruction of the left wrist led to arthrodesis.